Metafizyczna «natura» bytu matematycznego. Uwagi wstępne - Jerzy Tupikowski (Wrocławski Przegląd Teologiczny, 2020)
The fundamental goal of the analysis underlined in present article was initial presentation of the metaphysical conclusions relating to the being and the content of the mathematical being. Outlined conception of understanding of that being allows to draw two fundamental conclusions. First of all, the mathematical being finds its ground it in context of the role and of the realistic presentation specification of the concrete, real being with metaphysical equipment. The essential accent is the realism of existence of that being. Afterwards the mathematical being, as the effect of abstraction, shows itself as peripheral understanding of the concrete being, appearing its quantity aspect. This nature of the mathematical being exposes itself and exploits simultaneously it’s essence-understanding in the quantitative (mathematical) interpretation of the world. That interpretation is the important dimension specification of reality, which realizes varied types of features, elements, categories, where the quantitative structure constitutes the fundamental factor, which enables it’s realistic understanding.